2010
DOI: 10.1243/09544054jem1862
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Behaviour of the Green Particulate Fluid Lubricant in Its Nano Regime when Machining AISI 1040 Steel

Abstract: Significant advances, both practical and theoretical, have been made in understanding the behaviour of engineering materials when machining at higher cutting conditions. Nano-integrated manufacturing is a subject of immense interest for various sustainable engineered systems. Metal removal processes involve the generation of high cutting forces and temperatures. The use of proper lubricant to reduce forces and temperatures and to improve total cutting phenomena overall is an important aspect. The present inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…In addition to the chip morphology, average tool flank wear was also measured. Ramana et al 17 prepared petroleum-free lubricant by mixing two canola oil and nano-crystalline boric acid, and performance evaluation was carried out.…”
Section: Developed Al 2 O 3 /Ticmentioning
confidence: 99%
“…In addition to the chip morphology, average tool flank wear was also measured. Ramana et al 17 prepared petroleum-free lubricant by mixing two canola oil and nano-crystalline boric acid, and performance evaluation was carried out.…”
Section: Developed Al 2 O 3 /Ticmentioning
confidence: 99%
“…The phenomenon of de-creased surface quality in terms of particle size is proved in one of the works where solid particles of sizes ranging from micro to nano level were used during turning operations. The experimentations revealed that better surface finish is obtained when larger particle sizes in the nano regime are used [25].…”
Section: Tribologia -Finnish Journal Of Tribology 1-2 Vol 37/2020mentioning
confidence: 99%
“…3 Because of its extensive use, several studies have been conducted to investigate the machinability of AISI 1040 steel. [4][5][6][7] Using ML approaches has resulted in a significant improvement in the quality of the machining process for AISI 1040 steel. 8,9 Due to the time and technical constraints that exist in the industry today, conducting experiments at all parameters is not practicable.…”
Section: Introductionmentioning
confidence: 99%